Amplified fragment length polymorphism analysis supports the valid separate species status of Lucilia caesar and L. illustris (Diptera: Calliphoridae) - Christine J. Picard; Jeffrey D. Wells; Anne Ullyot; Knut Rognes (Forensic Sciences Research, 2018)
Common DNA-based species determination methods fail to distinguish some blow flies in the forensically and medically important genus Lucilia Robineau-Desvoidy. This is a practical problem, and it has also been interpreted as casting doubt on the validity of some morphologically defined species. An example is Lucilia illustris and L. caesar, which co-occur in Europe whilst only L. illustris has been collected in North America. Reports that these species shared both mitochondrial and nuclear gene sequences, along with claims that diagnostic morphological characters are difficult to interpret, were used to question their separate species status. We report here that amplified fragment length polymorphism profiles strongly support the validity of both species based on both assignment and phylogenetic analysis, and that traditional identification criteria based on male and female genital morphology are more reliable than has been claimed.